Privatization in State-Owned Enterprises: A Systematic Literature Review - Salma Shofia Rosyda; Sam'un Jaja Raharja (Universitas Padjadjaran, 2020)
One of the effective ways to improve the governance of State-Owned Enterprises (SOEs) is through privatization. A common problem that occurs at present in SOEs is that state-owned companies are inefficient in the use of resources, especially labor. The purpose of this research is to comprehend what is important in privatization, using the Systematic Literature Review (SLR) method. Some things that are important in the privatization of State-Owned Enterprises include privatization performance based on privatization activities, success factors, CSR in privatized SOEs, and performance after reducing government ownership. An improvement of performance both in terms of attainment and income along with a decrease in CSR were likely experienced by SOEs when privatizing. In addition, this research was also conducted to find out whether there were parts that had become worse after privatization. The privatization of SOEs was carried out by modernizing the economy. The decrease in performance of CSR could be minimized by social activities carried out by the company. The role of the government was very important in the supervision of SOEs so no one was able to gain personal benefit. The involvement of stakeholders was very important in this process because it could increase the trust of shareholders. During privatization, cooperating partners had to guarantee that there would be no termination of workers. In fact, it was hoped that more workers were to be added.